The role of cGAS-STING signaling in the development and therapy of head and neck squamous cell carcinoma - Shao, Chengze; Chen, Jiawen; Qiang, Bi; Ye, Junmei; Yan, Fangrong; Zhu, Yongbo (Frontiers in Immunology, 2024)
The cGAS-STING signaling pathway plays a critical role in innate immunity and defense against viral infections by orchestrating intracellular and adaptive immune responses to DNA. In the context of head and neck squamous cell carcinoma (HNSCC), this pathway has garnered significant attention due to its potential relevance in disease development and progression. HNSCC is strongly associated with risk factors such as smoking, heavy alcohol consumption, and human papillomavirus (HPV) infection. The presence or absence of HPV in HNSCC patients has been shown to have a profound impact on patient survival and prognosis, possibly due to the distinct biological characteristics of HPV-associated tumors. This review aims to provide a comprehensive overview of the current therapeutic approaches and challenges in HNSCC management, as well as the involvement of cGAS-STING signaling and its potential in the therapy of HNSCC. In addition, by advancing the present understanding of the mechanisms underlying this pathway, Activation of cGAS–STING-dependent inflammatory signaling downstream of chromosomal instability can exert both anti-tumoral and pro-tumoral effects in a cell-intrinsic manner, suggesting individualized therapy is of great importance. However, further exploration of the cGAS-STING signaling pathway is imperative for the effective management of HNSCC.